Application of Business Strategy to Create Competitive Advantage in Indonesian Micro, Small and Medium Enterprises - Grace Citra Dewi; Yulianah Yulianah; Ria Sandra Alimbudiono; Daniel Kurniawan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This research is the result of a review of the importance of formulating, designing, and implementing long-term strategies. The purpose of this research is to discuss how business strategies enable competitive advantage in organizations through their design, formulation, implementation, and control. This review was conducted as part of this research. Companies can no longer achieve a competitive advantage solely through the prices of their goods and/or services, nor can they achieve profitability in the short term; instead, their focus has shifted to the development of long-term strategies. Methodologies such as descriptive qualitative research from a theoretical point of view, analysis, synthesis, and documentary review of bibliographic references related to business strategy, as a generator of business competitive advantage, and how to achieve returns through long-term strategic planning are utilized in this study. As one of the conclusions, it is clear that the importance of developing, designing, and putting into action strategies that make it possible to achieve long-term results cannot be overstated, given that the role of managers is currently restricted to the production of financial performance.